Viral perturbations of host networks reflect disease etiology - Gulbahce, N; Yan, H; Dricot, A; Padi, M; Byrdsong, D; Franchi, R; Lee, D; Rozenblatt-Rosen, O; Mar, J; Calderwood, M; Baldwin, A; Zhao, B; et al. (Public Library of Science, 2012)
Many human diseases, arising from mutations of disease susceptibility genes (genetic diseases), are also associated with viral infections (virally implicated diseases), either in a directly causal manner or by indirect associations. Here we examine whether viral perturbations of host interactome may underlie such virally implicated disease relationships. Using as models two different human viruses, Epstein-Barr virus (EBV) and human papillomavirus (HPV), we find that host targets of viral proteins reside in network proximity to products of disease susceptibility genes. Expression changes in virally implicated disease tissues and comorbidity patterns cluster significantly in the network vicinity of viral targets. The topological proximity found between cellular targets of viral proteins and disease genes was exploited to uncover a novel pathway linking HPV to Fanconi anemia.